Fatal Biliary-Systemic Air Embolism during Endoscopic Retrograde Cholangiopancreatography: A Case with Multifocal Liver Abscesses and Choledochoduodenostomy - Cha, Sung Tae (Yonsei University College of Medicine, 2010)
We report a rare case of a massive fatal embolism that occurred in the middle of endoscopic retrograde cholangiopancreatography (ERCP) and retrospectively examine the significant causes of the event. The patient was a 50-year old female with an uncertain history of previous abdominal surgery for multiple biliary stones 20 years prior. The patient presented with acute right upper quadrant pain. An abdominal computed tomographic (CT) scan revealed the presence of multiple stones in the common bile duct (CBD) and intra-hepatic duct (IHD) with biliary obstruction, multifocal liver abscesses, and air-biliarygram. Emergency ERCP showed a wide and straight opening of choledochoduodenostomy, which may have been created during a previous surgery, and multiple filling defects in the CBD. With the use of a forward endoscope, mud stones were extracted through the opening of the choledochoduodenostomy. Cardiac arrest suddenly developed during the procedure, and despite immediate resuscitation, the patient died due to a massive systemic air embolism. We reviewed previously reported fatal cases and accessed factors facilitating air embolisms in this case.